Analysis of Superhydrophobic-Superoleophilic Properties on Modification of Polyurethane Sponge for Selective Oil-Water Separation - Niken Aprilia Eka Putri; Arif Tjahjono; Perdamean Sebayang (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2021)
In this research, a modification of polyurethane (PU) sponge material has been made to obtain superhydrophobic-superoleophilic properties. The PU sponge was coated with several nanomaterials such as ZnO, Fe3O4+TEOS, and stearic acid by dip-coating and drop-coating methods. The tests include selective separation of oil and water with a magnetic response. Several types of oil and organic solvents were tested for absorption capacity. The results showed that the PU@ZnO@Fe3O4@SA sponge has a good absorption capacity, from 4.37 mL to 7.37 mL. The fabricated PU sponge could selectively separate oil from water with a separation efficiency above 99%. The fabricated PU sponge also could be magnetically driven by external magnetic fields. From the characterization using 3D OM, the water contact angle was 153.38°, which indicates that the PU@ZnO@Fe3O4@SA sponge is superhydrophobic. And from surface morphology obtained an average pore size diameter of 167.475 μm.